Comparative Transcriptome Analysis of CMV or 2b-Deficient CMV-Infected dcl2dcl4 Reveals the Effects of Viral Infection on Symptom Induction in Arabidopsis thaliana - Qian Xu; Li Shen; Liying Jin; Meng Wang; Fenghan Chang; Zhongxin Guo (Viruses, 2022)
Due to the impaired antiviral RNAi, the dcl2dcl4 (dcl2/4) mutant is highly susceptible to viruses deficient of the viral suppressor of the RNA silencing (VSR) contrast to wild-type Arabidopsis. It was found that more severe disease symptoms were induced in dcl2/4 infected with VSR-deficient CMV (CMV-Δ2b or CMV-2aTΔ2b) compared to wild-type Arabidopsis infected with intact CMV. In order to investigate the underlying mechanism, comparative transcriptome analysis was performed with Col-0 and dcl2/4 that were infected by CMV, CMV-Δ2b and CMV-2aTΔ2b, respectively. Our analysis showed that the systematic infection of CMV, CMV-Δ2b and CMV-2aTΔ2b could cause hypoxia response and reduce photosynthesis. Asymptomatic infections of CMV-Δ2b or CMV-2aTΔ2b in Columbia (Col-0) promoted the expression of cell division-related genes and suppressed the transcription of metabolism and acquired resistance genes. On the other hand, immunity and resistance genes were highly induced, but photosynthesis and polysaccharide metabolism-related genes were suppressed in diseased plants. More interestingly, cell wall reorganization was specifically caused in modestly diseased Col-0 infected by CMV and a strong activation of SA signaling were correspondingly induced in severely diseased dcl2/4 by CMV or CMV mutants. Thus, our research revealed the nature of the Arabidopsis–CMV interaction at the transcriptome level and could provide new clues in symptom development and antiviral defense in plants.